Implementing Knowledge Management Strategies in Mpumalanga's Local Government: From Silos to Synergy - Mkhabela, LZ.; Moloi, KC; Isabirye, AK. (Journal of Ecohumanism, 2025)
This study examines the detrimental effects of silo mentality on knowledge management practices within Mpumalanga's local government. It seeks to propose strategies for enhancing synergy among municipal departments. The primary aim is to explore how fragmented operations hinder effective service delivery and to recommend mechanisms for fostering collaboration and integration across governmental entities. Utilising a qualitative literature review methodology, relevant data were sourced from authoritative publications, including those from South African Local Government Association (SALGA), the Local Government Sector Education Training Authority (LGSETA), and the Department of Cooperative Governance and Traditional Affairs (COGTA), emphasising works published in the last ten years. Key findings indicate that current government operations suffer from significant duplication and inefficiency due to a lack of coordinated knowledge sharing, resulting in weak accountability and poor service outcomes for communities. The study recommends consolidating governmental mandates and budgets into a unified plan aligned with the District Development Model (DDM) and emphasises the necessity of sharing knowledge across departments to optimise performance. Additionally, it highlights the need for an empirical study to validate these findings and further explore practical implementations of knowledge management strategies in local government settings. This research advocates for a transformative approach to municipal governance that prioritises collaboration and data-driven decision-making for enhanced public service delivery.